Impact of Moving Sign (Running Text) Implementation at PKBM Wiyata Utama - Julpri Andika; Yudhi Gunardi; Triyanto Pangaribowo; Heru Suwoyo; Muhammad Hafizd Ibnu Hajar; Ketty Siti Salamah; Zendi Iklima; Rachmat Muwardi (Universitas Mercu Buana, 2022)
The running information display board or Running Text is one of the information media or digital publications comprised of an ordered pattern of Light Emitting Diode (LED) lights, and each LED has a coordinate point that determines which LED position is on or off. This LED light is available in a range of colors, including red, yellow, green, blue, white, and blended hues. This running text is often used in Office Buildings, School Buildings, Shopping Buildings, and other locations where the general public must be informed. At this community service, running text has been installed in the PKBM Wiyata Utama school environment in Kembangan Utara, West Jakarta, which is suitable for school-related information media such as education level, school name, and school events